Gender and AI: Exploring the Intersection of Technology and Social Change (International Journal of Educational Management, Rivers State University., 2025)
The paper explored the intersection of gender and artificial intelligence (AI), examining how these dynamic shapes both technological development and societal transformation. It delved into the following key areas. Gender Bias in AI. The study analyzed how existing gender biases in data sets and algorithms can perpetuate and amplify societal inequalities within AI systems. It examined the implications of biased AI in areas like hiring, loan approvals, and criminal justice, highlighting the need for diverse perspectives and inclusive design principles. Women's Representation in AI. It examines the underrepresentation of women in AI research, development, and leadership roles. It explored the factors contributing to this disparity, including gender stereotypes, lack of mentorship, and systemic barriers. It also examined the impact of this underrepresentation on the development and deployment of AI technologies. AI's Potential for Gender Equality. The abstract explored the potential of AI to promote gender equality by addressing existing societal challenges. It examined how AI can be used to combat gender-based violence, improve access to education and healthcare, and empower women in the workforce. Ethical Considerations. The study discussed the ethical implications of AI development and deployment in relation to gender. It explored issues such as privacy, surveillance, and the potential for AI to exacerbate existing power imbalances. It emphasizes the need for ethical frameworks and regulations to ensure that AI technologies are developed and used responsibly. Future Directions. The study suggests, by outlining key areas for future research and action. It called for increased efforts to address gender bias in AI, promote women's participation in the field, and ensure that AI technologies are developed and deployed in a way that benefits all members of society.